If pth term of ap is q and qth term is p. p.t its nth term, Mathematics

If the pth term of an AP is q and the qth term is p. P.T its nth term is (p+q-n).

Ans:    APQ

ap = q

aq = p

an = ?

a + (p-1) d = q

a + (q-1) d = p

d[p - q] = q - p  Sub d = -1 to get ⇒ = -1 ⇒ a = q + p -1 an = a + (n - 1)d

= a + (n - 1)d

= (q + p - 1) + (n - 1) - 1 an = (q + p - n)

 

Posted Date: 4/8/2013 5:46:19 AM | Location : United States







Related Discussions:- If pth term of ap is q and qth term is p. p.t its nth term, Assignment Help, Ask Question on If pth term of ap is q and qth term is p. p.t its nth term, Get Answer, Expert's Help, If pth term of ap is q and qth term is p. p.t its nth term Discussions

Write discussion on If pth term of ap is q and qth term is p. p.t its nth term
Your posts are moderated
Related Questions
5:9 and 3:5 then find a:b:c?

John is planning to buy an irregularly shaped plot of land. Referring to the diagram, determine the total area of the land. a. 6,400 m 2 b. 5,200 m 2 c. 4,500 m 2 d.

Ask questutfjion #Minimum 100 words accepted#

Let R be the relation on Z + defined by aRb iff gcd(a; b) = 1 (that is, a and b have no common divisors greater than one). Explain whether R is reflexive, irreflexive, symmetri

Consider the clique graph below. a) How many subgraphs of G with 3 nodes are there?  b) How many of the subgraphs defined in part(a) are induced subgraphs?

Exponential Functions : We'll begin by looking at the exponential function,                                                              f ( x ) = a x We desire to differe

With reference to Fig. 1(a) show that the magnification of an object is given by M=SID/SOD. With reference to Fig. 1(b) show that the size of the penumbra (blur) f is given by f

If α & ß are the zeroes of the polynomial 2x 2 - 4x + 5, then find the value of a.α 2 + ß 2   b. 1/ α + 1/ ß  c. (α - ß) 2 d. 1/α 2 + 1/ß 2    e.  α 3 + ß 3 (Ans:-1, 4/5 ,-6,

A vertical post stands on a horizontal plane.  The angle of elevation of the top is 60 o and that of a point x metre be the height of the post, then prove that x = 2 h/3 .

Solving for X in isosceles triangles